Formulation of Encapsulated Extracts from Local Palu Red Onion Bulbs (Allium cepa var. aggregatum L.) Using Carrageenan Coating: Characterization, Stability, and Antioxidant Activity - Nurhaeni; Aulia Pariusi Pariusi; Aini Auliana Amar; Ruslan; Abdul Rahman Razak; Indriani (KOVALEN: Jurnal Riset Kimia, 2026)
This study aimed to identify the optimal concentration of carrageenan as a coating matrix for extracts of local Palu red onion bulbs (Allium cepa var. aggregatum L.) using the ion gelation method to characterise their properties, stability and antioxidant activity. The technique of converting liquid samples into small particles is known as microencapsulation. Carrageenan was formulated at varying concentrations (0.1%, 0.2%, 0.3%) with the addition of 0.1% Na-TPP. Testing of antioxidant activity at a concentration of 0.3% yielded the highest antioxidant activity of 87.59%. The ANOVA test results showed that the matrix concentration had a significant effect (<0.05) on antioxidant activity. A total phenolic content of 49.61 mg GAE/g was observed in the 0.3% carrageenan sample. Carrageenan was stable at temperatures of 25°C and 40°C. FTIR characterisation of the encapsulation process indicated the presence of spectra showing interactions between the coating matrix and the extract, revealing changes in functional groups. PSA analysis indicated a particle size of 2100 µm.